Interest in politics modulates neural activity in the amygdala and ventral striatum. - Gozzi, M; Zamboni, G; Krueger, F; Grafman, J (2010)
Studies on political participation have found that a person's interest in politics contributes to the likelihood that he or she will be involved in the political process. Here, we looked at whether or not interest in politics affects patterns of brain activity when individuals think about political matters. Using functional magnetic resonance imaging (fMRI), we scanned individuals (either interested or uninterested in politics based on a self-report questionnaire) while they were expressing their agreement or disagreement with political opinions. After scanning, participants were asked to rate each political opinion presented in the scanner for emotional valence and emotional intensity. Behavioral results showed that those political opinions participants agreed with were perceived as more emotionally intense and more positive by individuals interested in politics relative to individuals uninterested in politics. In addition, individuals interested in politics showed greater activation in the amygdala and the ventral striatum (ventral putamen) relative to individuals uninterested in politics when reading political opinions in accordance with their own views. This study shows that having an interest in politics elicits activations in emotion- and reward-related brain areas even when simply agreeing with written political opinions.